1995
DOI: 10.1037/1040-3590.7.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Assessment depression in primary care practice with the Beck Depression Inventory and the Hamilton Rating Scale for Depression.

Abstract: Individuals suffering from depression seek help as frequently in the primary care setting as in psychiatric facilities. As primary care physicians increasingly provide such treatments, they will need to assess a patient's clinical status before, during, and after treatment. The authors evaluated the concordance and factor structures of 2 widely used depression inventories, the Beck Depression Inventory and the Hamilton Rating Scale for Depression, in a sample of primary care patients participating in a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 46 publications
2
50
0
2
Order By: Relevance
“…All interviews were conducted independently by a psychodiagnostician. The HRSD is one of the most widely used, and best validated indexes of depressive symptoms (Brown, Schulberg, & Madonia, 1995;Sayer et al, 1993), and displays strong significant correlations with other scales measuring depression, including the Beck Depression Inventory (Beck, Steer, & Garbin, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…All interviews were conducted independently by a psychodiagnostician. The HRSD is one of the most widely used, and best validated indexes of depressive symptoms (Brown, Schulberg, & Madonia, 1995;Sayer et al, 1993), and displays strong significant correlations with other scales measuring depression, including the Beck Depression Inventory (Beck, Steer, & Garbin, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…insomnia, weight loss) and for overemphasizing cognitive symptoms of depression [69,70], we also administered the depression subscale of the Hamburg Modules for the Assessment of Psychosocial Health in Clinical Practice (HEALTH-49) [71]. The HEALTH-49 is an open-source instrument which is widely used in the German health care system.…”
Section: Methodsmentioning
confidence: 99%
“…The Hamilton scales for depression and anxiety have been used extensively in psychiatric research. Previous studies have contrasted the scale with the Beck Depression Inventory and found that the Hamilton scales assess the affective and somatic aspects of depression and anxiety [23] .…”
Section: Structured Clinical Interview Guide For the Hamilton Anxietymentioning
confidence: 99%